Conformational and stereoelectronic investigation of tryptamine : An AIM/NBO study - Lobayan, Rosana M. (2012)
Due to the free radical scavenger properties of Tryptamine (TRA), as well as of others indole derivatives, it is in our interest to explore deeply the stereoelectronic aspects that would be relevant in their stabilization and antioxidant activity. In this work the conformational space of TRA was scanned using molecular dynamics complemented with functional density calculations at B3LYP/6-31 + G** level. Twenty one conformers of lowest energy were obtained, their electronic distributions were analyzed at a higher calculation level, thus improving the basis set (B3LYP/6-311++G**). A topological study based on Bader’s theory (AIM: atoms in molecules) and natural bond orbital (NBO) framework was performed. The study was enriched by a deep analysis of maps of molecular electrostatic potential (MEP) through a coordinated NBO/AIM analysis. The conformational preferences were explained by hyperconjugative interactions, which were revealed by NBO data. Because radical scavenging by indolic compounds is strongly modulated by their functional residues our study was related to similar analysis done previously on Indole and 1H-indole-3-acetic acid (IAA). Therefore, the conformational space of TRA was studied from a new perspective focusing on a deep analysis of the geometric and electronic properties of TRA conformers. The changes of the electronic distribution introduced by the substituent and the conformational flexibility of the side chain were addressed. The results reported contribute to the understanding of the structure, stability and reactivity of TRA and others indole derivatives.